Nanopolystyrene beads affect motility and reproductive success of oyster spermatozoa (Crassostrea gigas) - Tallec, K.; Paul-Pont, Ika; Boulais, M.; Le Goïc, Nelly; Le Grand, Fabienne; Bideau, Antoine; Quéré, C.; Cassone, A.-L.; González-Fernández, Carmen; Lambert, Christophe; Soudant, Philippe; Huvet, Arnaud (Nanotoxicology, 2020)
WOS:000560848100001 International audience Oysters are keystone species that use external fertilization as a sexual mode. The gametes are planktonic and face a wide range of stressors, including plastic litter. Nanoplastics are of increasing concern because their size allows pronounced interactions with biological membranes, making them a potential hazard to marine life. In the present study, oyster spermatozoa were exposed for 1 h to various doses (from 0.1 to 25 mu g mL(-1)) of 50-nm polystyrene beads with amine (50-NH(2)beads) or carboxyl (50-COOH beads) functions. Microscopy revealed adhesion of particles to the spermatozoa membranes, but no translocation of either particle type into cells. Nevertheless, the 50-NH(2)beads at 10 mu g mL(-1)induced a high spermiotoxicity, characterized by a decrease in the percentage of motile spermatozoa (-79%) and in the velocity (-62%) compared to control spermatozoa, with an overall drop in embryogenesis success (-59%). This major reproduction failure could be linked to a homeostasis disruption in exposed spermatozoa. The 50-COOH beads hampered spermatozoa motility only when administered at 25 mu g mL(-1)and caused a decrease in the percentage of motile spermatozoa (-66%) and in the velocity (-38%), but did not affect embryogenesis success. Microscopy analyses indicated these effects were probably due to physical blockages by microscale aggregates formed by the 50-COOH beads in seawater. This toxicological study emphasizes that oyster spermatozoa are a useful and sensitive model for (i) deciphering the fine interactions underpinning nanoplastic toxicity and (ii) evaluating adverse effects of plastic nanoparticles on marine biota while waiting for their concentration to be known in the environment.